Job-Related Strain and Sexual Health Difficulties among Heterosexual Men from Three European Countries: The Role of Culture and Emotional Support - Štulhofer, Aleksandar (Array, 2013)
Although clinical literature has suggested a link between job-related stress and sexual difficulties in men, epidemiological evidence for this association is largely lacking. Moreover, little is known about the factors that may mediate or moderate the impact of workplace strain on sexual health. This study analyzes the association between job-related difficulties and men's sexual difficulties. Analyses were carried out using data from an online study carried out in 2011 on convenience samples of Portuguese, Croatian, and Norwegian men (N = 2, 112). Multivariate logistic regression and mediation analysis were used to test the hypothesized associations. Job-related difficulties were measured by ten yes/no questions that addressed a range of adverse workplace situations. The experience of sexual difficulties in the past 12 months was assessed by using seven dichotomous indicators developed in the NATSAL 2000 study. Men with job-related concerns reported lower sexual satisfaction than men without such concerns did (F = 7.53, P < .001). Multivariate analysis confirmed the association between job-related and sexual health concerns. The odds of experiencing one or more sexual health difficulties in the past 12 months were about 1.8 times higher among men who reported the highest levels of workplace difficulties than among men who experienced no such difficulties. The odds of reporting sexual health differences were significantly reduced by a higher income (adjusted OR = .87, P < .01), emotional intimacy with one's partner (AOR = .93, P < .001), having children (AOR = .62-.66, P < .01), and country-specific effects (AOR = 1.98-2.22, P < .001). In all three countries, the relationship between job-related and sexual health difficulties was mediated by negative mood (anxiety and depression), but no evidence was found for the moderating role of emotional support (intimacy and fatherhood).